After Disclosure: A Research Protocol to Respond to Disclosures of Abuse and Sexual Violence in Research With Adults With Intellectual Disabilities. Issue 4 (3rd April 2019) - Sammet Moring, Nechama; Parish, Susan L.; Mitra, Monika; Alterio, Nancy A.
Abstract: People with intellectual disabilities (ID) have high lifetime risk of abuse and assault, including sexual violence. As adults with ID participate in research, researchers must be prepared for disclosures of past or current abuse. In collaboration with our state's protective agency, we developed a protocol for responding effectively to disclosures of sexual violence from adult research participants with ID. We completed a literature review clarifying best practices for responding to disclosures of abuse by adults with ID. The literature focused on various professionals but we were unable to find evidence clarifying researchers' roles in responding to sexual violence. Working with our state protective services agency, we adapted these practices to develop protocols and an algorithm for responding to disclosure, as well as materials for participants. Our protocol for abuse reporting considers all members of the research team to be mandated reporters, emphasizes informed consent, and details specific steps for responding to disclosures of abuse in the context of research. It represents a collaboration between academic researchers and community partners. Research participation by people with ID may represent an opportunity for disclosure of past or current abuse, and therefore, it is imperative that researchers are equipped to respond effectively. Policy‐level responses to prevent abuse and enable justice are also needed; however, ensuring that researchers respond systematically and effectively to disclosures is crucial to the ethical conduct of research with a vulnerable population. We anticipate that the frequency with which researchers will need to use this protocol will depend on the nature of their research. In practice, we recommend including this protocol as part of the overall study protocol and submitting it for Institutional Review Board (IRB) approval. Future research to test our protocol in the field is recommended.